Streak camera imaging of single photons at telecom wavelength - Allgaier, Markus; Ansari, Vahid; Eigner, Christof; Quiring, Viktor; Ricken, Raimund; Donohue, John Matthew; Czerniuk, Thomas; Aßmann, Marc; Bayer, Manfred; Brecht, Benjamin; Silberhorn, Christine (Applied Physics Letters)

Quantum-Limited Time-Frequency Estimation through Mode-Selective Photon Measurement - Donohue, J. M.; Ansari, V.; Řeháček, J.; Hradil, Z.; Stoklasa, B.; Paúr, M.; Sánchez-Soto, L. L.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Electromagnetically Induced Transparency of On-demand Single Photons in a Hybrid Quantum Network - Schweickert, Lucas; Jöns, Klaus D.; Namazi, Mehdi; Cui, Guodong; Lettner, Thomas; Zeuner, Katharina D.; Montaña, Lara Scavuzzo; Silva, Saimon Filipe Covre da; Reindl, Marcus; Huang, Huiying; Trotta, Rinaldo; Rastelli, Armando; et al. (arXiv:1808.05921)
Long range quantum communication and quantum information processing require the development of light-matter interfaces for distributed quantum networks. Even though photons are ideal candidates for network links to transfer quantum information, the system of choice for the realization of quantum nodes has not been identified yet. Ideally, one strives for a hybrid network architecture, which will consist of different quantum systems, combining the strengths of each system. However, interfacing different quantum systems via photonic channels remains a major challenge because a detailed understanding of the underlying light-matter interaction is missing. Here, we show the coherent manipulation of single photons generated on-demand from a semiconductor quantum dot using a rubidium vapor quantum memory, forming a hybrid quantum network. We demonstrate the engineering of the photons' temporal wave function using four-level atoms and the creation of a new type of electromagnetic induced transparency for quantum dot photons on resonance with rubidium transitions. Given the short lifetime of our quantum dot transition the observed dynamics cannot be explained in the established steady-state picture. Our results play a pivotal role in understanding quantum light-matter interactions at short time scales. These findings demonstrate a fundamental active node to construct future large-scale hybrid quantum networks.

Manipulation of Two-Photon Interference by Entanglement - Sharapova, Polina; Luo, Kai Hong; Herrmann, Harald; Reichelt, Matthias; Silberhorn, Christine; Meier, Torsten (Conference on Lasers and Electro-Optics)

Incomplete Detection of Nonclassical Phase-Space Distributions - Bohmann, M.; Tiedau, J.; Bartley, Tim; Sperling, Jan; Silberhorn, Christine; Vogel, W. (Physical Review Letters)

Monolithically Integrated Hong-Ou-Mandel Experiment in LiNbO3 - Luo, Kai Hong; Brauner, Sebastian; Eigner, Christof; Sharapova, Polina; Ricken, Raimund; Meier, Torsten; Herrmann, Harald; Silberhorn, Christine (Conference on Lasers and Electro-Optics)

Imaging of 180∘ ferroelectric domain walls in uniaxial ferroelectrics by confocal Raman spectroscopy: Unraveling the contrast mechanism - Rüsing, Michael; Neufeld, Sergej; Brockmeier, Julian; Eigner, Christof; Mackwitz, P.; Spychala, K.; Silberhorn, Christine; Schmidt, Wolf Gero; Berth, Gerhard; Zrenner, Artur; Sanna, S. (Physical Review Materials)
In recent years, Raman spectroscopy has been used to visualize and analyze ferroelectric domain structures. The technique makes use of the fact that the intensity or frequency of certain phonons is strongly influenced by the presence of domain walls. Although the method is used frequently, the underlying mechanism responsible for the changes in the spectra is not fully understood. This inhibits deeper analysis of domain structures based on this method. Two different models have been proposed. However, neither model completely explains all observations. In this work, we have systematically investigated domain walls in different scattering geometries with Raman spectroscopy in the common ferroelectric materials used in integrated optics, i.e., KTiOPO4, LiNbO3, and LiTaO3. Based on the two models, we can demonstrate that the observed contrast for domain walls is in fact based on two different effects. We can identify on the one hand microscopic changes at the domain wall, e.g., strain and electric fields, and on the other hand a macroscopic change of selection rules at the domain wall. While the macroscopic relaxation of selection rules can be explained by the directional dispersion of the phonons in agreement with previous propositions, the microscopic changes can be explained qualitatively in terms of a simplified atomistic model.

Volumetric Generation of Optical Vortices with Metasurfaces - Huang, Lingling; Song, Xu; Reineke, Bernhard; Li, Tianyou; Li, Xiaowei; Liu, Juan; Zhang, Shuang; Wang, Yongtian; Zentgraf, Thomas (ACS Photonics)

Zn–VI quasiparticle gaps and optical spectra from many-body calculations - Riefer, Arthur; Weber, Nils; Mund, Johannes; Yakovlev, Dmitri R.; Bayer, Manfred; Schindlmayr, Arno; Meier, Cedrik; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)
The electronic band structures of hexagonal ZnO and cubic ZnS, ZnSe, and ZnTe compounds are determined within hybrid-density-functional theory and quasiparticle calculations. It is found that the band-edge energies calculated on the G0W0 (Zn chalcogenides) or GW (ZnO) level of theory agree well with experiment, while fully self-consistent QSGW calculations are required for the correct description of the Zn 3d bands. The quasiparticle band structures are used to calculate the linear response and second-harmonic-generation (SHG) spectra of the Zn–VI compounds. Excitonic effects in the optical absorption are accounted for within the Bethe–Salpeter approach. The calculated spectra are discussed in the context of previous experimental data and present SHG measurements for ZnO.

Fabrication of low-loss Rb-exchanged ridge waveguides in z-cut KTiOPO_4 - Volk, Martin F.; Rüter, Christian E.; Santandrea, Matteo; Eigner, Christof; Padberg, Laura; Herrmann, Harald; Silberhorn, Christine; Kip, Detlef (Optical Materials Express)

A monolithic, doubly-resonant parametric down-conversion source for Caesium Raman memories - Brecht, Benjamin; Lazo-Arjona, O.; Kaczmarek, K. T.; Parker, T.; Ricken, R.; Quiring, V.; Eigner, Christof; Luo, K. H.; Herrmann, Harald; Silberhorn, Christine; Walmsley, I. A. (Frontiers in Optics 2017)

Waveguide Cavity Resonator as a Source of Optical Squeezing - Stefszky, M.; Ricken, R.; Eigner, Christof; Quiring, V.; Herrmann, Harald; Silberhorn, Christine (Physical Review Applied)

A two-channel, spectrally degenerate polarization entangled source on chip - Sansoni, Linda; Luo, Kai Hong; Eigner, Christof; Ricken, Raimund; Quiring, Viktor; Herrmann, Harald; Silberhorn, Christine (npj Quantum Information)

Heteroepitaxy of III–V Zinc Blende Semiconductors on Nanopatterned Substrates - Riedl, Thomas; Lindner, Jörg (Nanoscaled Films and Layers)
In the last decade, zinc blende structure III–V semiconductors have been increasingly utilized for the realization of high‐performance optoelectronic applications because of their tunable bandgaps, high carrier mobility and the absence of piezoelectric fields. However, the integration of III–V devices on the Si platform commonly used for CMOS electronic circuits still poses a challenge, due to the large densities of mismatch‐related defects in heteroepitaxial III–V layers grown on planar Si substrates. A promising method to obtain thin III–V layers of high crystalline quality is the growth on nanopatterned substrates. In this approach, defects can be effectively eliminated by elastic lattice relaxation in three dimensions or confined close to the substrate interface by using aspect‐ratio trapping masks. As a result, an etch pit density as low as 3.3 × 10^5 cm^−2 and a flat surface of submicron GaAs layers have been accomplished by growth onto a SiO2 nanohole film patterned Si(001) substrate, where the threading defects are trapped at the SiO2 mask sidewalls. An open issue that remains to be resolved is to gain a better understanding of the interplay between mask shape, growth conditions and formation of coalescence defects during mask overgrowth in order to achieve thin device quality III–V layers

Joining self-assembly techniques: A route to hierarchical nanopores - Brassat, Katharina; Lindner, Jörg

Micro- and nanopatterned surfaces with tailored chemical and topographical contrast by self-assembly techniques - Brassat, Katharina; Kool, Daniel; Bürger, Julius; Lindner, Jörg

Tailored antidot patterns created by nanosphere lithography for bioapplications - Brassat, Katharina; Keller, A.; Grundmeier, G.; Bremser, W.; Strube, O.; Lindner, Jörg

Morphological properties of nanopillar patterned Si surfaces obtained by nanosphere lithography and metal-assisted wet-chemical etching - Kismann, Michael; Riedl, Thomas; Lindner, Jörg

InAs heteroepitaxy on GaAs patterned by nanosphere lithography - Kunnathully, Vinay; Riedl, Thomas; Karlisch, A.; Reuter, Dirk; Lindner, Jörg

Group III arsenide heteroepitaxy on Si(111) using SiNx nanohole masks patterned by nanosphere lithography - Riedl, Thomas; Kunnathully, Vinay; Karlisch, A.; Reuter, Dirk; Lindner, Jörg

Morphology, structure and enhanced PL of molecular beam epitaxial In0.2Ga0.8As layers on nanopillar patterned GaAs - Riedl, Thomas; Kunnathully, Vinay; Karlisch, A.; Reuter, Dirk; Weber, N.; Meier, Cedrik; Schierholz, R.; Lindner, Jörg

Strain and strain energy in axial-heteroepitaxial GaAs/InAs nanopillars analyzed by atomistic and continuum elastic calculations - Riedl, Thomas; Lindner, Jörg

The influence of the sphere material on the opening size distribution of nanosphere lithography masks - Riedl, Thomas; Lindner, Jörg

Evolution of the opening size of nanosphere lithography masks during thermal annealing - Riedl, Thomas; Kunnathully, Vinay; Lindner, Jörg

Strain Compensation in Single ZnSe/CdSe Quantum Wells: Analytical Model and Experimental Evidence - Rieger, Torsten; Riedl, Thomas; Neumann, Elmar; Grützmacher, Detlev; Lindner, Jörg; Pawlis, Alexander (ACS Applied Materials & Interfaces)

Strain effects on the heteroepitaxy of III-V compound semiconductors on nanopatterned surfaces - Lindner, Jörg; Riedl, Thomas

Ion Beam Modification of Self-Organized Nanostructures - Lindner, Jörg

Bioinspired material design by hierarchical self-assembly on prepatterned surfaces - Brassat, Katharina; Keller, A.; Grundmeier, G.; Bremser, W.; Strube, O.; Lindner, Jörg

Regular surface nanopatterning with nanosphere lithography, block copolymer lithography and cominations of both - Brassat, Katharina; Brodehl, Christoph; Lindner, Jörg

Directional Emission from Dielectric Leaky-Wave Nanoantennas - Peter, Manuel; Hildebrandt, Andre; Schlickriede, Christian; Gharib, Kimia; Zentgraf, Thomas; Förstner, Jens; Linden, Stefan (Nano Letters)
Keywords: tet_topic_opticalantenna

Double resonant plasmonic nanoantennas for efficient second harmonic generation in zinc oxide - Weber, Nils; Protte, Maximilian; Walter, Felicitas; Georgi, Philip; Zentgraf, Thomas; Meier, Cedrik (Physical Review B)

Ultrathin Nonlinear Metasurface for Optical Image Encoding - Walter, Felicitas; Li, Guixin; Meier, Cedrik; Zhang, Shuang; Zentgraf, Thomas (Nano Letters)

Identifying and Realizing Symmetries in Quantum Walks - Symmetry Classes and Quantum Walks - Schütte, Philipp

Two-dimensional switchable blue phase gratings manufactured by nanosphere lithography - Wahle, M.; Brassat, Katharina; Ebel, J.; Bürger, Julius; Lindner, Jörg; Kitzerow, Heinz-Siegfried (Optics Express 25)
Switchable two dimensional liquid crystal diffraction gratings are promising can- didates in beam steering devices, multiplexers and holographic displays. For these areas of applications a high degree of integration in optical systems is much sought-after. In the context of diffraction gratings this means that the angle of diffraction should be rather high, which typically poses a problem as the fabrication of small grating periods is challenging. In this paper, we propose the use of nanosphere lithography (NSL) for the fabrication of two-dimensionally structured electrodes with a periodicity of a few micrometers. NSL is based on the self-assembly of micro- or nanometer sized spheres into monolayers. It allows for easy substrate structuring on wafer scale. The manufactured electrode is combined with a liquid crystalline polymer-stabilized blue phase, which facilitates sub-millisecond electrical switching of the diffraction efficiency at adiffractionangle of 21.4°.

Plasmonic nanostructures: spectroscopy and electron microscopy - Kitzerow, Heinz-Siegfried; Lindner, Jörg

Limits of the time-multiplexed photon-counting method - Kruse, Regina; Tiedau, Johannes; Bartley, Tim; Barkhofen, Sonja; Silberhorn, Christine (Physical Review A)

Driven Boson Sampling - Barkhofen, Sonja; Bartley, Tim; Sansoni, Linda; Kruse, Regina; Hamilton, Craig S.; Jex, Igor; Silberhorn, Christine (Physical Review Letters)

High-Efficiency Plug-and-Play Source of Heralded Single Photons - Montaut, Nicola; Sansoni, Linda; Meyer-Scott, Evan; Ricken, Raimund; Quiring, Viktor; Herrmann, Harald; Silberhorn, Christine (Physical Review Applied)
Keywords: General Physics and Astronomy

Extracting the physical sector of quantum states - Mogilevtsev, D; Teo, Y S; Řeháček, J; Hradil, Z; Tiedau, J; Kruse, R; Harder, G; Silberhorn, Christine; Sanchez-Soto, L L (New Journal of Physics)
Keywords: General Physics and Astronomy

Harnessing temporal modes for multi-photon quantum information processing based on integrated optics - Harder, G.; Ansari, V.; Bartley, Tim; Brecht, Benjamin; Silberhorn, Christine (Philosophical Transactions of the Royal Society A: Mathematical, Physical and Engineering Sciences)
In the last few decades, there has been much progress on low loss waveguides, very efficient photon-number detectors and nonlinear processes. Engineered sum-frequency conversion is now at a stage where it allows operation on arbitrary temporal broadband modes, thus making the spectral degree of freedom accessible for information coding. Hereby the information is often encoded into the temporal modes of a single photon. Here, we analyse the prospect of using multi-photon states or squeezed states in different temporal modes based on integrated optics devices. We describe an analogy between mode-selective sum-frequency conversion and a network of spatial beam splitters. Furthermore, we analyse the limits on the achievable squeezing in waveguides with current technology and the loss limits in the conversion process. This article is part of the themed issue ‘Quantum technology for the 21st century’.

Fast time-domain measurements on telecom single photons - Allgaier, Markus; Vigh, Gesche; Ansari, Vahid; Eigner, Christof; Quiring, Viktor; Ricken, Raimund; Brecht, Benjamin; Silberhorn, Christine (Quantum Science and Technology)

Time-resolved photon echoes from donor-bound excitons in ZnO epitaxial layers - Poltavtsev, S. V.; Kosarev, A. N.; Akimov, I. A.; Yakovlev, D. R.; Sadofev, S.; Puls, J.; Hoffmann, S. P.; Albert, M.; Meier, Cedrik; Meier, Torsten; Bayer, M. (Physical Review B)

Toolbox for the design of LiNbO3-based passive and active integrated quantum circuits - Sharapova, Polina; Luo, Kai Hong; Herrmann, Harald; Reichelt, Matthias; Meier, Torsten; Silberhorn, Christine (New Journal of Physics)

Modified two-photon interference achieved by the manipulation of entanglement - Sharapova, Polina; Luo, Kai Hong; Herrmann, Harald; Reichelt, Matthias; Silberhorn, Christine; Meier, Torsten (Physical Review A)

Toolbox for the design of LiNbO3-based passive and active integrated quantum circuits - Sharapova, Polina; Luo, Kai Hong; Herrmann, Harald; Reichelt, Matthias; Meier, Torsten; Silberhorn, Christine (New Journal of Physics)

Towards integrated superconducting detectors on lithium niobate waveguides - Höpker, Jan Philipp; Bartnick, Moritz; Meyer-Scott, Evan; Thiele, Frederik; Meier, Torsten; Bartley, Tim; Krapick, Stephan; Montaut, Nicola M.; Santandrea, Matteo; Herrmann, Harald; Lengeling, Sebastian; Ricken, Raimund; et al. (Quantum Photonic Devices)

Phase sensitive properties and coherent manipulation of a photonic crystal microcavity - Quiring, Wadim; Jonas, Björn; Förstner, Jens; Rai, Ashish K.; Reuter, Dirk; Wieck, Andreas D.; Zrenner, Artur (Optics Express)
We present phase sensitive cavity field measurements on photonic crystal microcavities. The experiments have been performed as autocorrelation measurements with ps double pulse laser excitation for resonant and detuned conditions. Measured E-field autocorrelation functions reveal a very strong detuning dependence of the phase shift between laser and cavity field and of the autocorrelation amplitude of the cavity field. The fully resolved phase information allows for a precise frequency discrimination and hence for a precise measurement of the detuning between laser and cavity. The behavior of the autocorrelation amplitude and phase and their detuning dependence can be fully described by an analytic model. Furthermore, coherent control of the cavity field is demonstrated by tailored laser excitation with phase and amplitude controlled pulses. The experimental proof and verification of the above described phenomena became possible by an electric detection scheme, which employs planar photonic crystal microcavity photo diodes with metallic Schottky contacts in the defect region of the resonator. The applied photo current detection was shown to work also efficiently at room temperature, which make electrically contacted microcavities attractive for real world applications.
Keywords: tet_topic_phc

Fabrication of fully undercut ZnO-based photonic crystal membranes with 3D optical confinement - Hoffmann, Sandro Phil; Albert, Maximilian; Meier, Cedrik (Superlattices and Microstructures)

Low-voltage DNTT-based thin-film transistors and inverters for flexible electronics - Meyers, Thorsten; Vidor, Fábio F.; Brassat, Katharina; Lindner, Jörg; Hilleringmann, Ulrich (Microelectronic Engineering)
In this article we present an integration technique for low-voltage DNTT-based TFTs for flexible electronic applications. Therefore, a high-k nanocomposite combining the flexibility of its polymericmatrix and the high permittivity of the incorporated inorganic material was used as gate dielectric layer. The influence of a conventional photolithography process upon the dielectric layer is analyzed regarding electrical instabilities in the device characteristics. The impact of an implemented sacrificial layer to reduce chemical stress to the insulating film during photolithography is evaluated. Furthermore, first inverter circuits were integrated and electrically characterized. Additionally, the implementation of this sacrificial layer can be used for future complementary circuit design.

Enzyme mediated autodeposition of protein particles on nanosphere lithographically nanostructured surfaces - Brassat, Katharina; Rüdiger, Arne; Bürger, Julius; Bremser, W.; Strube, Oliver; Lindner, Jörg